2x-1-9/7=-3x/4-x/3

Simple and best practice solution for 2x-1-9/7=-3x/4-x/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-1-9/7=-3x/4-x/3 equation:


x in (-oo:+oo)

2*x-(9/7)-1 = (-3*x)/4-(x/3) // - (-3*x)/4-(x/3)

2*x-((-3*x)/4)+x/3-(9/7)-1 = 0

2*x+(3/4)*x+x/3-9/7-1 = 0

37/12*x-16/7 = 0 // + 16/7

37/12*x = 16/7 // : 37/12

x = 16/7/37/12

x = 192/259

x = 192/259

See similar equations:

| 2601+b^2=3600 | | 200+11x=120+x^2 | | 40k+100=30k+140 | | 1x-8+14x=-34 | | p+3.1=18 | | x-27=62 | | -6y/2+2/2+3y/2=-10y/8+8/8 | | 6x-2=1.25(3x-8) | | 11-6x=6x-1 | | x+7.4=23.5 | | 12z+(13z-14)=-(26z-25)-9+20z | | 60=z-113 | | 11-6x=6c-1 | | 2X-14=-8 | | m+10/-2=5 | | -2x+6(2-x)-4=3(x+1)-6 | | -4y/3+6=-y/2+3 | | 6x-9+2x=79 | | 3(4K+7)=19K | | 9x=37.8 | | s+1.3=18 | | 6x+15=3x+3 | | a=-169/-13 | | 4/3+2Y=4Y-1/6 | | 23-9y+(26y-19)=-27 | | 3*1.8+1.2=6*1.8-0.3 | | -2x/2-12/2+7/4-3x/8-9/8 | | -4-6x+7x=-3 | | 12x-13x(x+4)=4x-6 | | (5.6p+.3p)+7.1=-2.2 | | 4(5y+3)=3(2y-5)- | | -14+t=26.5 |

Equations solver categories